Praca salezjańska z młodzieżą niedostosowaną społecznie postrzegana z punktu widzenia paradygmatycznych podstaw współczesnej resocjalizacji - Stańkowski , Bogdan Wiesław; Pindel , Edyta (Seminare. Poszukiwania naukowe, 2022)
In this article, the authors tackle the issue of Salesian social rehabilitation perceived from the point of view of the paradigmatic foundations of contemporary social rehabilitation. The scientific goal of this article is to look at the Salesian preventive system through the prism of the paradigmatic foundations in modern social rehabilitation. The article is based on the analysis of available literature on the subject. The analyzes undertaken allow to state that the Salesian preventive system fits into the paradigms of social rehabilitation in the Polish context. Therefore, the presented analyzes prove that this system correlates with paradigms functioning in contemporary social rehabilitation practiced in relation to socially maladjusted youth.